Inventario de la vegetación de la isla de Coiba, Panamá: composición y florística - Pérez, Rolando (1996)
Mature and Iittle-altered forest cover large expanses of the central and northem regions of Coiba island, Panamá (7°29' N; 8 1°45' W). A total of 231 species of plants, 203 of which were trees and shrubs, were recorded. The families with the most species were Leguminosae, Rubiaceae, and Melastomataceae. The higher elevation forest of the island center is dominated by Calophyllum longifolium, Eschweilera pittieri. Cassipourea elliptica, and Ternstroemia tepezapote, while Calophyllum longifolium. Tetragastris panamensis, and Carapa guianensis predominate in the surrounding, low-Iying foresto Pelliciera rhizophora and Rhizophora mangle are the most cornmon species of the mangrove forests along the southero shore of the island, and freshwater swamps are characterized by high densities of Prioria copaifera and Peltogyne purpurea. Within the variegated forest in the northero part of the island, we estabIished two 20 x 20 ro plots. Within each plot we rnarked and rneasured the diameter at breast height (dbh) of all woody plants greater than 1 cm dbh, excluding lianas. One plot yielded 29 species and 156 sterns, while the other had 37 species and 158 sterns. These levels of diversity are relatively low when compared to sarne-sized plots &oro comparable forest areas on mainland Panama.